Bioactive Cellulose Acetate Electrospun Mats as Scaffolds for Bone Tissue Regeneration - Laboy-López, Simara; Méndez Fernández, Pedro O.; Padilla-Zayas, Jorge G.; Nicolau, Eduardo (International Journal of Biomaterials, 2022)
In the last decades, cell-based approaches for bone tissue engineering (BTE) have relied on using models that cannot replicate the complexity of the bone microenvironment. There is an ongoing amount of research on scaffold development responding to the need for feasible materials that can mimic the bone extracellular matrix (ECM) and aid bone tissue regeneration (BTR). In this work, a porous cellulose acetate (CA) fiber mat was developed using the electrospinning technique and the mats were chemically modified to bioactivate their surface and promote osteoconduction and osteoinduction. The mats were characterized using FTIR and SEM/EDS to validate the chemical modifications and assess their structural integrity. By coupling adhesive peptides KRSR, RGD, and growth factor BMP-2, the fiber mats were bioactivated, and their induced biological responses were evaluated by employing immunocytochemical (ICC) techniques to study the adhesion, proliferation, and differentiation of premature osteoblast cells (hFOB 1.19). The biological assessment revealed that at short culturing periods of 48 hours and 7 days, the presence of the peptides was significant for proliferation and adhesion, whereas at longer culture times of 14 days, it had no significant effect on differentiation and maturation of the osteogenic progenitor cells. Based on the obtained results, it is thus concluded that the CA porous fiber mats provide a promising surface morphology that is both biocompatible and can be rendered bioactive upon the addition of osteogenic peptides to favor osteoconduction leading to new tissue formation.